From paper to action in climate change mitigation and adaptation: The case of the coffee rust in Chiapas - Libert-Amico, Antoine; Paz-Pellat, Fernando (Instituto de Ecología, A.C., 2018)
In the process of recognizing the multiple challenges that climate change presents to society and the environment, the number of studies, plans, and programs that discuss mitigation and adaptation has increased exponentially. Although a complex problem demands complex solutions, barriers to interdisciplinary visions and intersectoral coordination persist. Particularly, office-based projects (paper) rarely reach the implementation stage (action), while few contemplate the synergies between mitigation and adaptation. This article analyses climate change plans and programs for the coffee sector considering the coffee rust epidemic, a disease caused by the fungus Hemileia vastatrix which has generated important losses to coffee production since the 2012/2013 cycle. Structural problems created ideal conditions for this disease which has been associated with climate change, whilst the institutional response has generated new challenges for coffee producing communities who live in biodiversity hotspots like the Chiapas Sierra Madre in southern Mexico. We discuss the synergies between climate change mitigation and adaptation by analyzing the campaign in favor of carbon stocks and biodiversity in shade-grown coffee plantations of the Sierra Madre de Chiapas. Designed in response to the current coffee rust epidemic, this campaign emphasizes deforestation, forest degradation and loss of ecosystem services that is associated with the current crisis of shade-grown coffee, with proposals set out to benefit both ecosystems and the coffee communities. We identify three challenges which mark the distance between paper and action, as exemplified in the case of the coffee crisis in the Chiapas Sierra Madre.